The Applicability and Performance of Tools Used to Assess the Father-Offspring Relationship in Relation to Parental Psychopathology and Offspring Outcomes - Siew, Jasmine; Iles, Jane; Domoney, Jill; Bristow, Florence; Darwin, Zoe J.; Sethna, Vaheshta (Frontiers in Psychiatry, 2021)
Introduction: Father-infant interactions are important for optimal offspring outcomes. Moreover, paternal perinatal psychopathology is associated with psychological and developmental disturbances in the offspring, and this risk may increase when both parents are unwell. While, the father-offspring relationship is a plausible mechanism of risk transmission, there is presently no ‘gold standard’ tool for assessing the father-offspring relationship. Therefore, we systematically searched and reviewed the application and performance of tools used to assess the father-offspring relationship from pregnancy to 24-months postnatal. Methods: Four electronic databases (including MEDLINE, PsycINFO, Maternity & Infant Care Database and CINAHL) were searched. Selected articles included evidence of father-offspring relationship assessment in relation to parental perinatal psychopathology and/or offspring outcomes. Data was extracted and synthesized according to the following: i) evidence supporting the performance of tools in terms of their psychometric properties when applied in the context of fathers, ii) tool specific characteristics, and iii) study specific methodological aspects in which the tool was embedded. Results: Of the 30, 500 records eligible for screening, 38 unique tools used to assess the father-offspring relationship were identified, from 61 studies. 10 tools were employed in the context of paternal psychopathology, three in the context of maternal psychopathology, and seven in the context of both maternal and paternal psychopathology, while nine tools were applied in the context of offspring outcomes only. The remaining nine tools were used in the context of both parental psychopathology (i.e., paternal, and/or maternal psychopathology) and offspring outcomes. Evidence supporting the psychometric robustness of the extracted observational, self-report and interview-based tools was generally limited. Most tools were originally developed in maternal samples – with few tools demonstrating evidence of content validation specific to fathers. Furthermore, various elements influencing tool performance were recognized – including variation in tool characteristics (e.g. relationship dimensions assessed, assessment mode and scoring formats) and study specific methodological aspects, (e.g. setting and study design, sample characteristics, timing and nature of parental psychopathology and offspring outcomes). Conclusion: Future studies may benefit from a multi-method approach to assessing the father-offspring relationship, which may provide a more accurate assessment than one method alone.